Inclusion, diversity, equity and accessibility in the built environment: A study of architectural design practice. (December 2021) - Zallio, Matteo; Clarkson, P. John
Abstract: Accessibility is generally recognised as an important element of architectural design practice. However, studies suggest that the adoption of Inclusive Design by the architectural design community is still quite limited. Inclusive Design embraces the principles of accessibility and its extended definition considers key sociological and behavioural aspects such as physical, sensory and cognitive needs. This paper presents the results of an ethnographic study, conducted amongst 26 professionals from the building industry, on the adoption of Inclusive Design. This research aims to explore the challenges and limitations that professionals experience in their daily working practice and to identify strategies to expand the use of Inclusive Design and its extended definition. The findings emphasise how education and awareness are essential factors to encourage an inclusive mindset amongst architectural design professionals and other stakeholders. In particular, holistically mapping the user journey during the design phase and collecting and evaluating post-occupancy user feedback are complementary strategies that can foster a design process based on inclusion, diversity, equity and accessibility principles for the built environment. Highlights: Inclusive Design is still not widely adopted in architectural design practice. Building inclusively should embrace inclusion, diversity, equity and accessibility. Education is key to help foster inclusion in architectural design practice. User journey mapping can improve the Inclusive Design process. Post-occupancy user feedback can help architects to better design for inclusion.